The Board Independence and Performance Nexus: The Moderating Role of Firm Size - Mirayani, Luh Putri Mas (Jurnal Ilmiah Akuntansi & Bisnis, 2025)
This study examines the relationship between board independence and firm performance, emphasizing the moderating role of firm size in Indonesia’s manufacturing sector during 2021-2023. Grounded in Agency Theory, the research investigates how the proportion of independent commissioners affects Return on Assets (ROA) and whether firm size influences this relationship. Using a quantitative causal-associative approach with 177 firm-year observations from 59 listed manufacturing companies on the Indonesia Stock Exchange (IDX), the data were analyzed through Moderated Regression Analysis (MRA) after passing all classical assumption tests. The findings reveal that a higher proportion of independent commissioners significantly improves firm profitability (ROA). However, firm size negatively moderates this relationship, meaning that the positive effect of board independence weakens as firms grow larger. This result indicates that independent commissioners are more effective in smaller firms where their monitoring and advisory functions can operate without bureaucratic constraints, while in larger firms, their influence is limited by managerial entrenchment and structural complexity. Theoretically, this study enriches Agency Theory by demonstrating that board independence does not have a uniform impact but depends on organizational context specifically, firm size. Practically, the results encourage regulators and investors to move beyond a “one-size-fits-all” governance framework by strengthening the actual capacity and authority of independent commissioners in large corporations.